PENERAPAN CHSE DI HOTEL SALAK THE HERITAGE BOGOR - Cindy H Posumah; Mellia Jeneetica; Yuyun Krisnawati (Lembaga Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Pariwisata Bogor, 2020)
World wide covid-19 pandemic is affecting human behavior in travelling. The impact from this pandemic is declining tourism activity and causing some hotels closed. Adaptation to new habits or we call it New Normal is one of the best way to survive in pandemic situation. People implement New Normal -new lifestyle at home, outside, daily activity, non-routine traveling activity. This makes people change their lifestyle and more selective to do traveling activity. For example they will choose hotel, tourism destination, or restaurant with the best cleanliness and safety assurance. To achieve that, Indonesian government through tourism minister makes program called CHSE certification to hotel, tourism destination, restaurant, and creative industry. CHSE is Cleanliness, Health, Safety, and Environtment Sustainability. This research is held in Hotel Salak the Heritage Bogor as one of famous star-hotel in front of Bogor Presidential Palace. This research use qualitative descriptive method with secondary data analisys that available in Hotel Salak the Heritage Bogor with research tools checklist sheets. The result is Hotel Salak the Heritage Bogor meet the standard of CHSE and got CHSE certificate and labeling I DO CARE from Indonesian government. It can be concluded that Hotel Salak the Heritage Bogor implement CHSE that make people trust and feel secure/safe to do activity in Hotel.